Weakly compactly generated Frechet spaces - Surjit Singh Khurana (International Journal of Mathematics and Mathematical Sciences)
It is proved that a weakly compact generated Frechet space is Lindelöf in the weak topology. As a corollary it is proved that for a finite measure space every weakly measurable function into a weakly compactly generated Frechet space is weakly equivalent to a strongly measurable function.